2021
DOI: 10.1111/nicc.12729
|View full text |Cite
|
Sign up to set email alerts
|

Solid oral medications' suitability for use in enteral feeding tubes

Abstract: Background: There is a lack of specific data about the efficacy and safety of medications administered via feeding tubes, although there is a general awareness that not all drug formulations are suitable.Aims and objectives: To overview the current situation with solid medications administered through feeding tubes in the Tartu University Hospital intensive care units. To evaluate the availability of information on the suitability of drug formulations for administration via feeding tubes.Design: This was a des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…This project aimed to develop an easy-to-use tabular guideline for HCPs presenting all relevant information for oral medications used by patients with dysphagia. A small local study in TUH [5] and an additional literature review have demonstrated the need for the guideline described above.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This project aimed to develop an easy-to-use tabular guideline for HCPs presenting all relevant information for oral medications used by patients with dysphagia. A small local study in TUH [5] and an additional literature review have demonstrated the need for the guideline described above.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of clear and readily available information from drug manufacturers on ways to administrate medications to patients with dysphagia [4,5]. Although some handbooks and databases provide guidelines about medication management for these patients, much such information is unavailable [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other papers in this issue focus on pain intensity during treatment and care procedures 11 and after discharge from ICU 12 ; enteral nutrition practices by ICU nurses 13 ; medication administration through enteral feeding tubes 14 ; the development of an oral care frequency assessment scale 15 ; and ICU nurses' knowledge and practice regarding maintaining arterial catheter patency 16 …”
mentioning
confidence: 99%
“…Guner and Kutluturkan's randomized controlled trial adds to the growing body of evidence about the optimum angle of the head of bed elevation that is safe and effective in the prevention of ventilator-associated pneumonia, 9 while Burey et al investigated the feasibility of alveolar collapse analysis by measuring lung impedance distribution by nurses caring for patients with acute respiratory distress syndrome. 10 The other papers in this issue focus on pain intensity during treatment and care procedures 11 and after discharge from ICU 12 ; enteral nutrition practices by ICU nurses 13 ; medication administration through enteral feeding tubes 14 ; the development of an oral care frequency assessment scale 15 ; and ICU nurses' knowledge and practice regarding maintaining arterial catheter patency. 16 The authors of these papers employed various quantitative and qualitative methodologies, varying from randomized controlled trials and prospective observational studies to cross-sectional studies and survey design, and from document analysis and retrospective service evaluation to narrative inquiry.…”
mentioning
confidence: 99%